Biodegradability of SCOBY-derived bacterial cellulose affected by purification methods - Diego Gomez-Maldonado; Diego González Rodríguez; Mireya Valdés Rivera; Mariana Zerón Pontones; Edgar Ulin; Gabriel Vigueras-Ramírez; Maribel Hernández-Guerrero (Materials Research Express)
The mounting demand for sustainable biopolymers has prompted extensive research on bacterial cellulose (BC) as a prospective material for biomedical, food, and packaging applications. However, the impact of purification methods on BC biodegradability remains to be elucidated. This study explores the impact of purification treatments, including sodium hydroxide (NaOH) at 1 wt%, 8 wt%, and 16.5 wt%, and ethanol (96%), on the biodegradation of symbiotic culture of bacteria and yeast (SCOBY) derived BC. Biodegradability was evaluated under controlled soil conditions in a bioclimatic chamber and in media inoculated with wastewater through CO _2 quantification by gas chromatography. The findings suggest that the lowest NaOH concentration (1 wt%) effectively eliminates microorganisms while sustaining high biodegradation rates. Conversely, higher NaOH concentrations impede degradation due to residual alkaline effects. Ethanol-treated BC exhibited the fastest degradation in compost, presumably due to enhanced fibril accessibility, although residual ethanol impacted microbial activity. CO _2 analysis corroborated microbial activity, with NaOH-treated samples demonstrating the highest CO _2 production in the inoculated mineral media. These findings underscore the significance of purification techniques in modulating BC biodegradability and optimize purification methods could enhance BC’s potential for environmentally friendly applications, particularly where controlled degradation is necessary.